2018
DOI: 10.5005/jp-journals-10033-1338
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Laparoscopy as an Effective Tool in Evaluation of Intra-abdominal Malignancies

Abstract: Accurate diagnosis and staging are crucial in defining an effective plan of management in intra-abdominal malignancies. Despite the availability of a wide array of imaging techniques, a high incidence of nontherapeutic procedures have been observed. Laparoscopy finds its utility in reducing this discrepancy by an accurate assessment of the extent of the disease. This review article explores applications of laparoscopy in the staging and diagnosis of abdominal malignancy and its comparative advantages against i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Patients with suspicious malignancy may not reach the secondary care on time, or they may be reach the wrong specialty [49]. This study is in agreement with Vivek Tiwari et al, A K Dwivedi et al and Mohammed et al [50][51][52] Few other related studies were reported [53][54][55][56][57].…”
Section: Association Of Operative and Pathological Findingssupporting
confidence: 89%
“…Patients with suspicious malignancy may not reach the secondary care on time, or they may be reach the wrong specialty [49]. This study is in agreement with Vivek Tiwari et al, A K Dwivedi et al and Mohammed et al [50][51][52] Few other related studies were reported [53][54][55][56][57].…”
Section: Association Of Operative and Pathological Findingssupporting
confidence: 89%
“…Surgery and anaesthesia induce shivering as a compensatory mechanism due to thermal dysregulation, which is exacerbated by spinal anaesthesia vasodilatation that redistributes core body heat. We also found in our sample that the number of patients complaining of shivering in the simple Bupivacaine group was significantly high compared to the clonidine group 29. Few studies also reflected on anaesthetics used lower abdominal surgeries [30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…An important goal of this technique is to reduce the number of negative laparotomies and reduce the surgical burden in patients who appear to have resectable abdominal masses. This results in reduced perioperative morbidity and mortality, shorter hospital stays, and earlier referral to chemoradiotherapy (Yeola et al, 2018).…”
Section: O M P a R A T I V E S T U D Y O F D N A P L O I D Y A N D B ...mentioning
confidence: 99%